PRO-HEALTH BEHAVIOURS AND BELIEF IN ONESELF AMONG 13-15-YEAR OLD TEENAGERS LIVING IN BIALA PODLASKA - Rafal Grad (Kharkov National Pedagogical University, 2013)
The aim of the research was to get information about pro-health behaviours and belief in oneself among 13-15-year old teenagers living in Biała Podlaska. The research included 229 pupils from three Grammar Schools (115 girls and 114 boys). The range of respondents' age varied from 13 to 15 years old. The research tool was two anonymous questionnaires. The first questionnaire contained questions concerning teenagers' belief in themselves and the efficacy of their activities (10 statements). The second questionnaire referred to the pro-health behaviours and it consisted of 14 situations described in the form of multiple choice questions. It was shown that Grammar School goers higly evaluated their own sense of efficacy (31,2 points). Girls (30,39 points) in comparison to boys (32,05) evaluated their efficacy lower by 1,66 points. Grammar School goers in 85,7% of cases choose healthy behaviours and girls are the group which reach for such behaviours more often.